Infant Colic - : Possible Causes and Treatment - Buczek, Agnieszka; Ptasiński, Aleksander; Niekurzak, Rafał; Suława, Adrian; Targoński, Oskar; Targońska, Marta; Furgalska, Julia; Fedorowicz, Sebastian; Basiak, Aneta (Quality in Sport, 2024)
Introduction and Purpose: Infant colic (IC) is an ailment that refers to many infants until the age of 5 months of life. It is manifested by crying that start and stop without any obvious cause, irritability, paroxsyms, curling the legs and body flexing. Until today, there is said, that occurring of IC is multifactorial. [6,7]. Our aim is to show possible causes of infant colic and ways of treatment. Our article was based on the PubMed database. State of Knowledge: Many studies show that there is no one reason that causes infant colic and that there are some methods that may help baby relieve the colic pain. Factors that can have affect on occurring IC are allergy on cow’s milk, immature digestive system of newborns, disbiosis of intestine microbiota. [1,5] Some kind of methods may contain manual therapies, such as craniosacral therapy, gut microbiota that inhabit intestines of newborns and infants, mother’s diet and supplementation of lactase. [1,2] Summary: This review describes that manual therapy such as craniosacral therapy, gut microbiota containing supplementation BB-12 and Lactobacillus rhamnosus ATCC, supplementation of lactase and mother’s elimination diet has positive impact on babies and help them reduce symptoms of infant colic resulting in baby’s health and parent’s tranquility. [3,9]